Challenges of urbanization in areas susceptible to flooding: Case study in Residencial Lindalma Soares, Teresina - PI (Research, Society and Development, 2025)
This article aims to analyze the socio-environmental challenges of urbanization in high-risk areas, based on the case study of Residencial Lindalma Soares, which is located in an area susceptible to flooding in the Parque Brasil neighborhood, in the municipality of Teresina, State of Piauí (PI), Brasil. The irregular occupation present in the research area, which began in 2019, occurred without adequate urban planning in accordance with the land use and occupation order, resulting in precarious constructions and increased vulnerability of the population residing in the neighborhood. The methodology included a survey of cartographic data, temporal images from Google Earth and analysis in QGIS. The results highlight the lack of basic infrastructure, the risks of natural disasters, such as floods and landslides, and the difficulties faced by the community due to socioeconomic and environmental precariousness. The study concludes that integrated actions between the public authorities and civil society are necessary to mitigate risks and promote sustainable urban development.